I am looking for a proof of the problem as following:

Let $f(x)$ is a real continuous function that is strictly convex ($f''>0$) on $[m, M]$, let $m \le x_i \le M$, for $i=1,2,\ldots,n$ then show that:

$$nf\left(\frac{x_1+\cdots+x_n}{n}\right)+n\left(\frac{f(M)+f(m)}{2}-f\left(\frac{M+m}{2}\right)\right) \ge f(x_1)+\cdots+f(x_n)$$

Equality holds if only if $m=x_1=x_2=\cdots=x_n=M$

  • 1
    $\begingroup$ Equality holds if [and] only if ... The only if part can't be true. Equality trivially holds for a constant function no matter what $m, M, x_i$ for example. $\endgroup$ – dxiv Aug 19 '16 at 3:05
  • $\begingroup$ @dxiv The function that is convex, so the function is not a constant function $\endgroup$ – Oai Thanh Đào Aug 19 '16 at 3:24
  • 1
    $\begingroup$ A constant function is convex (and concave, for that matter). I guess what you have in mind is a strictly convex function, see the definitions at mathworld or wikipedia for example. If you do mean a strictly convex function then you should edit the question and spell it out. $\endgroup$ – dxiv Aug 19 '16 at 3:29
  • 1
    $\begingroup$ Your edit f'' > 0 introduces the assumption that the function would have a 2nd order derivative, which is a far stronger assumption than the original one of continuity. Why not simply call it for what it is - a *strictly* convex function - and leave derivatives out of the picture. $\endgroup$ – dxiv Aug 19 '16 at 3:40

The inequality does not hold in general. For a simple counterexample, consider the convex function:

$$ f(x) = \begin{cases} 0 & \text{if $x \lt \frac{2}{3}$} \\ x - \frac{2}{3} & \text{if $x \ge \frac{2}{3}$} \end{cases} $$

and $m=0, M=1, n=3, x_1=0, x_2=x_3=1$.

Since $f(0)=f(\frac{1}{2})=f(\frac{2}{3})=0, f(1)=\frac{1}{3}$ the inequality becomes:

$$ 3 f(\frac{2}{3}) + 3(\frac{f(0)+f(1)}{2} - f(\frac{1}{2})) \ge f(0) + 2 f(1) $$ $$ \frac{1}{2} \ge \frac{2}{3} $$ where the latter is obviously false.

For a counterexample using a strictly convex function, one can choose $f(x) = e^x$, $m = 0 \le M$, $n=3$, $x_1=0, x_2=x_3=M$. The inequality becomes:

$$ 3 e^{\frac{2}{3}M} + 3(\frac{1+e^M}{2} - e^\frac{M}{2}) \ge 1 + 2 e^M $$

$$ - \frac{1}{2} e^M + 3 e^{\frac{2}{3}M} - 3 e^\frac{M}{2} + \frac{1}{2} \ge 0 $$

The latter will fail for large enough $M$ since the dominant term $e^M$ has a negative coefficient.

  • 1
    $\begingroup$ Dear Mister @dxiv, Thank to You, see here mathoverflow.net/questions/247930/… $\endgroup$ – Oai Thanh Đào Aug 22 '16 at 4:02
  • $\begingroup$ @OaiThanhĐào Thank you for the followup. The new formulation posted at MO looks right, indeed. $\endgroup$ – dxiv Aug 22 '16 at 4:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.